Agenda for Building a New Financial Market Architecture - Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Since the summer of 2007, participants in financial markets have been confronted by a crisis of their own making. In order to prevent the recurrence of a similar crisis in the future, the G-20 nations, at their finance summit in Washington on 15 November 2008, resolved to "ensure that all financial markets, products and participants are regulated or subject to oversight, as appropriate to their circumstances." However, the elimination of loopholes as a matter of principle does not in itself provide a roadmap for the reconfiguration of financial markets. DIW Berlin is promoting an agenda of nine principles for regulatory reform. Item 1 through 3 focus on the prevention of coordination failures at the micro and the macro level as well as establishing appropriate incentives front and center; item 4 through 6 sketch out opportunities and limits for the future role of government; item 7 and 8 focus on oversight. Finally, item 9 calls for a stronger emphasis on equity financing and makes an appeal for the insight that financing constraints based upon credit worthiness ultimately serve to protect the financial system.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: G20; G24; G28; 330; Financial crisis; Regulation; Financial architecture